The Relationship Between Slogan Prints on Apparel and Consumer Self-Expression - Effendi, Rachel Audrey; Kim, Boyeun (VCD: Journal of Visual Communication Design, 2024)
Besides serving a purpose as clothing, slogan apparel is also a form of communication for self-expression. This paper researches consumers’ awareness and intention of self-expression through slogan apparel and consumers’ comfort levels with various types of slogans written on the apparel they wear. This research was conducted with a quantitative methodology which includes an online survey on Gen Z and millennials who wear slogan apparel from several countries. The result shows that consumers who wear slogan apparel are aware of self-expression through slogan apparel, but contradictingly their intention of self-expression through slogan apparel is low. Moreover, consumers’ comfort level with wearing slogan apparel varies on the type of slogan written on the apparel.